2020
DOI: 10.2147/cmar.s251605
|View full text |Cite
|
Sign up to set email alerts
|

<p>Not All Hepatocellular Carcinoma Patients with Microvascular Invasion After R0 Resection Could Be Benefited from Prophylactic Transarterial Chemoembolization: A Propensity Score Matching Study</p>

Abstract: Background: Prophylactic transarterial chemoembolization (p-TACE) is strongly recommended for hepatocellular carcinoma (HCC) patients with microvascular invasion (MVI), but the potential beneficiaries remain controversial. Methods: Data of HCC patients with MVI who underwent R0 resection between December 2013 and December 2015 were identified through the primary liver cancer big data. Disease-free survival (DFS) and overall survival (OS) were compared between patients who received p-TACE or not using Kaplan-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…( 29 ) considered p-TACE, a safe intervention, which reduced tumor recurrence rates and improved the OS for MVI using a high-quality meta-analysis. In contrast, the recent results showed that only patients with Barcelona Clinic Liver Cancer (BCLC) stage A, China Liver Cancer (CNLC) stage Ib, and American Joint Commission on Cancer (AJCC) stage II were found to benefit more from p-TACE, but not patients with BCLC stage 0/B, CNLC stage IIb, and AJCC stage IIIa ( 30 ). A part of studies declared that p-TACE was not inferior to more cycles when improving prognosis, strongly recommending only one cycle following R0 resection ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…( 29 ) considered p-TACE, a safe intervention, which reduced tumor recurrence rates and improved the OS for MVI using a high-quality meta-analysis. In contrast, the recent results showed that only patients with Barcelona Clinic Liver Cancer (BCLC) stage A, China Liver Cancer (CNLC) stage Ib, and American Joint Commission on Cancer (AJCC) stage II were found to benefit more from p-TACE, but not patients with BCLC stage 0/B, CNLC stage IIb, and AJCC stage IIIa ( 30 ). A part of studies declared that p-TACE was not inferior to more cycles when improving prognosis, strongly recommending only one cycle following R0 resection ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, the recent results showed that only patients with Barcelona Clinic Liver Cancer (BCLC) stage A, China Liver Cancer (CNLC) stage Ib, and American Joint Commission on Cancer (AJCC) stage II were found to benefit more from p-TACE, but not patients with BCLC stage 0/B, CNLC stage IIb, and AJCC stage IIIa ( 30 ). A part of studies declared that p-TACE was not inferior to more cycles when improving prognosis, strongly recommending only one cycle following R0 resection ( 30 , 31 ). Moreover, Liu et al.…”
Section: Discussionmentioning
confidence: 94%
“…In China, the prophylactic TACE is the main anti-recurrence strategy for HCC but remains with controversies. Some clinical studies have shown that HCC patients with PVTT receiving prophylactic TACE after radical surgery could effectively prolong the recurrence-free survival time of about 2.4 months when compared with those without prophylactic TACE treatment, but other studies indicated that this treatment had poor anti-recurrence effect and considerable toxicity [ 20 23 ]. Therefore, it is extremely necessary to develop novel effective and safe anti-recurrence strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[26]considered p-TACE as a safe intervention which reduced tumour recurrence rates and improved the OS for MVI using highquality meta-analysis.Besides,the recent results showed that only patients with BCLC stage A, CNLC stage Ib, and AJCC stage II both were found to be bene ted more from p-TACE, but not patients with BCLC stage 0/B, CNLC stage IIb, and AJCC stage IIIa [27].Contrastingly, they declared that p-TACE was not inferior to more cycles when improving prognosis, strongly recommending only one cycle following R0 resection [27,28].…”
Section: Transarterial Chemoembolization(tace)mentioning
confidence: 99%